2020
DOI: 10.5713/ajas.19.0958
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genetic diversity and population structure of 22 chicken breeds in Asia using microsatellite markers

Abstract: A c c e p t e d A r t i c l e 2 ABSTRACT 52Objectives: Estimating the genetic diversity and structures, both within and among chicken 53 breeds, is critical for the identification and conservation of valuable genetic resources. In 54 chickens, microsatellite (MS) marker polymorphisms have previously been widely used to 55 evaluate these distinctions. Our objective was to analyze the genetic diversity and 56 relationships among 22 chicken breeds in Asia based on allelic frequencies. 57 Methods: We used 469 geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…However, microsatellites and DNA barcodes still accepted as markers of choice because they are technically less demanding and cost-effective in evaluation. Ample literature is available on use of microsatellite markers in domestic chicken [29][30][31]. Nonetheless, uses of SNP markers and whole mitogenome sequencing have recently been appeared in the publication, which can be used to evaluate genetic diversity of domestic chicken.…”
Section: Discussionmentioning
confidence: 99%
“…However, microsatellites and DNA barcodes still accepted as markers of choice because they are technically less demanding and cost-effective in evaluation. Ample literature is available on use of microsatellite markers in domestic chicken [29][30][31]. Nonetheless, uses of SNP markers and whole mitogenome sequencing have recently been appeared in the publication, which can be used to evaluate genetic diversity of domestic chicken.…”
Section: Discussionmentioning
confidence: 99%
“…This haplogroup is widely distributed in red junglefowl in Thailand [44], whereas it is comparatively rare in domestic chickens and has only been reported in a limited number of indigenous chickens in Indonesia [50] and Thailand [44]. These results thus indicate that In a number of previous studies, the genetic diversity of indigenous chickens in Southeast Asia has been investigated using microsatellite DNA markers [18,20,44,51]. For example, Cuc et al ( 2010) [18] examined the genetic diversity of nine indigenous chicken breeds in Vietnam and found that the mean number of alleles per locus (Na), observed heterozygosity (Ho), and expected heterozygosity (He) were 6.09, 0.60, and 0.63, respectively.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 83%
“…and four breeds from Laos (0.62 to 0.69 and 0.64 to 0.68, respectively) [20] but were less than 0.60 in nine Thai indigenous chicken breeds (averaging 0.56 and 0.57, respectively) [44]. In…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%
See 2 more Smart Citations